Perception of health professionals from a city in the interior of Brazil on the vulnerability of older adults to hiv infection - Lima, Patrícia Aparecida Borges de; Rezende, Carlos Henrique Alves de; Hattori, Wallisen Tadashi; Pinto, Rogério de Melo Costa (Brazilian Journal of Sexually Transmitted Diseases, 2018)
Introduction: Discussing the AIDS/Older adult theme is a challenging task, as it contradicts the common association of old age with "asexuality", added to the difficulty in early diagnosis when considering other common comorbidities in this age group. Objective: To know the perception of health professionals regarding the possibility of HIV/AIDS infection in older patients. Methods: This cross-sectional observational study received a favorable opinion (19072313.9.0000.5152) from the Human Research Ethics Committee (Universidade Federal de Uberlândia – UFU). Dentists, nurses, and physicians from the Primary Care Network participated. We applied Questionnaire 1 to 15 professionals and analyzed the content to elaborate Questionnaire 2, applied to 220 professionals. Results: In the χ2 test of independence, the professionals presented a response pattern similar to that expected for most items, indicating that the profession does not determine the Yes or No answer. The exploratory factor analysis identified dimensions and allowed us to eliminate items that did not contribute to the formation of these dimensions. After three attempts, we found five factors and kept only highly correlated items (r>0.5) in the antiimage matrix. Nine of the 25 items were excluded. We performed a multivariate mixed general linear model (professions x factors). An interaction effect between factors and profession was found for factors 2 (Lack of professional engagement), 3 (Lack of engagement of public management), and 5 (Stigma). Discussion: The results suggest similarities and differences in the responses given by health professionals, showing the influence of both common and specific training base of these professionals. Conclusion: Older adults are vulnerable due to the non-use of condoms, a practice known to most health professionals. AIDS in old age is not the focus of care in public health services, given the low participation of some professions in the public system and their lack of knowledge, considering the old curricula in educational institutions, which do not offer disciplines to expand the training of this professional.